Perioperative Effects of Different Narcotic Analgesics Used to Improve Effectiveness of Total Intravenous Anaesthesia - (:unkn) unknown (AVES, 2016)
Objective: We aimed to evaluate the depth of anaesthesia, perioperative haemodynamics, postoperative pain scores, analgesic consumption in patients receiving remifentanil-or alfentanil-based total intravenous anaesthesia for single-level lumbar discectomy. Methods: Seventy patients undergoing discectomy were enrolled in the study. Patients were intravenously administered an initial bolus dose of 2 mg kg(-1) propofol and 10 mcg kg(-1) alfentanil or 1 mcg kg(-1) remifentanil, followed by 6 mg kg(-1) h(-1) propofol and either 1 mcg kg(-1) min(-1) alfentanil or 0.25 mcg kg(-1) min(-1) remifentanil infusion. Bispectral index (BIS) values, mean arterial pressure, heart rate, end-tidal carbon dioxide and oxygen saturation were recorded. Postoperative pain scores at 0, 30 and 60 min were measured and recorded with additional opioid requirements. Results: Postoperative pain scores at 0 and 30 min, total analgesic consumption and requirement for additional analgesics were significantly high in the remifentanil group. After the first hour, the pain scores were not significantly different. Mean arterial blood pressure was significantly low at 45 and 60 min preoperatively in the remifentanil group. In the remifentanil group, heart rate at 15, 30, 45, 60 min were significantly lower than those in the alfentanil group. BIS values of the two groups were not significantly different at any measurement time point. BIS values of remifentanil group at 30, 45, 60, 90 and 180 min significantly increased compared with those at 15 min. Conclusion: Alfentanil provided more stable BIS and haemodynamic values preoperatively and less opioid consumption, along with lower pain scores, during the early postoperative period compared with remifentanil in patients undergoing single-level discectomy.
Keywords: Remifentanil; alfentanil; propofol; bispectral index; TIVA; anaesthesia; BISPECTRAL INDEX; REMIFENTANIL; ALFENTANIL; PAIN; DISKECTOMY; SURGERY; COST